Onset of flow instability with one-side heated swirl tube for fusion reactor safety. (15th December 2021) - Lim, Ji Hwan; Lee, Su Won; Oh, Hoongyo; Park, Minkyu; Hwang, Donkoan; Kim, Moo Hwan; Jo, HangJin
Abstract: In this study, the onset of flow instability (OFI) heat flux of a one-side heated swirl tube is experimentally investigated. The OFI heat flux means the minimum heat flux that can cause flow instability by the vapor generated in the flow path. An analysis of the effect of system parameters on the OFI heat flux indicates that as the pressure increases, the bubble size decreases. Therefore, the void fraction decreases and, consequently, the OFI heat flux tends to increase. Similarly, the higher the flow rate and degree of subcooling, the faster the vapor can be removed; thus, the OFI heat flux increases. In addition, the prediction performances of the existing OFI correlations developed under the subcooled flow-boiling condition are evaluated. Therefore, although the Wang correlation indicates the lowest error rate, it yields a high mean absolute error rate of 87.75%. Thus, it is difficult to predict the OFI heat flux of a one-side heated swirl tube using the existing OFI correlations. Therefore, in this study, a new correlation is developed using a Python code created by employing an artificial intelligence regression method. The developed correlation incorporates the impact of one-side heating, swirl tape, mass flow rate, subcooling, and pressure (mean absolute error = 12.17%, root mean square error = 14.99%).